2008
DOI: 10.1051/0004-6361:20078611
|View full text |Cite
|
Sign up to set email alerts
|

Metallicities and activities of southern stars

Abstract: Aims. We present the results from high-resolution spectroscopic measurements to determine metallicities and activities of bright stars in the southern hemisphere. Methods. We measured the iron abundances ([Fe/H]'s) and chromospheric emission indices (log hR HK ) of 353 solar-type stars with V = 7.5−9.5. [Fe/H] abundances are determined using a custom χ 2 fitting procedure within a large grid of Kurucz model atmospheres. The chromospheric activities were determined by measuring the amount of emission in the cor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
123
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 116 publications
(138 citation statements)
references
References 40 publications
13
123
2
Order By: Relevance
“…This result shows that no mechanism causing line asymmetries seems to be responsible for the observed RV signal. In addition, we computed stellar chromospheric activity, as described in Jenkins et al (2008Jenkins et al ( , 2011. The results are plotted in Fig.…”
Section: Line Profile Analysis and Stellar Photometric Variabilitymentioning
confidence: 99%
“…This result shows that no mechanism causing line asymmetries seems to be responsible for the observed RV signal. In addition, we computed stellar chromospheric activity, as described in Jenkins et al (2008Jenkins et al ( , 2011. The results are plotted in Fig.…”
Section: Line Profile Analysis and Stellar Photometric Variabilitymentioning
confidence: 99%
“…This was determined using the distance from the Hipparcos main sequence as a function of B − V colour where we set all subgiants to have a distance from the main sequence of 1 or greater. The full selection details are explained in Jenkins et al (2008), hereafter referred too as Paper I. Therefore, this plot merely serves to highlight the sample distribution we will discuss in the chapters that follow.…”
Section: Observations and Reductionmentioning
confidence: 99%
“…Such fundamental characterisation is also necessary for a more complete understanding of stellar populations and galactic structure. Studies of stellar chromospheric activity in large samples of nearby stars (Duncan et al 1991;Henry et al 1996;Wright 2004;Jenkins et al 2006Jenkins et al , 2008 have found that the magnetic activity of solar type dwarfs and subgiants follows a bimodal distribution. In addition, the activity of Based on observations made with the ESO telescopes at the La Silla Paranal observatory under programme ID's 076.C-0578(B), 077.C-0192(A), 082.C-0446(A) and 082.C-0446(B).…”
Section: Introductionmentioning
confidence: 99%
“…FEROS has a resolving power of R ∼ 48 000, an efficiency of ∼20% and provides an almost complete optical spectral coverage (∼3500−9200 Å), which allows us to study many absorption lines in the optical range (used in the chemical analisys and in our radial velocity computations) and also to study the emission in the core of the Ca ii HK lines (3933 and 3968 Å), which are used as chromospheric activity indicators (e.g. Jenkins et al 2008, and references therein). The echelle spectrograph mounted on the 1.5 m telescope, can reach a maximum resolution of R ∼ 45 000 with an efficiency of ∼1% and covers a spectral region between 4020 Å and 7100 Å.…”
Section: Observations and Data Reductionmentioning
confidence: 99%